2022
DOI: 10.26599/bsa.2022.9050009
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal bisphenol A exposure impairs the aversive and spatial memory reduces the level of NMDA receptor subunits in the hippocampus of male Sprague Dawley rats

Abstract: Memory impairment in children is an ongoing issue worldwide related to a learning disability. This neurobiological condition has been suggested to associate with bisphenol A (BPA) exposure during pregnancy. BPA is an inorganic compound used to produce polycarbonate plastics and epoxy resins. We conduct this study to investigate the effects of prenatal BPA exposure on the level of the N-methyl-D-aspartate (NMDA) receptor subunits, synaptic markers of the hippocampus and neurobehavioral outcomes in rats. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…To prove that the modulation of miRNA and mRNA could affect brain function, we speci cally analyzed the memory retention ability of the rats at the adolescent level (AD35). The present result was comparable with our previous nding, where prenatal BPA exposure at 5 mg/kg/day induced anxietyrelated behavior and impaired learning and memory function 41 . The open eld test is considered to cause anxiety in animals due to social isolation and fear of the novel environment, and the outcome can be altered based on the lighting condition 42,43 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…To prove that the modulation of miRNA and mRNA could affect brain function, we speci cally analyzed the memory retention ability of the rats at the adolescent level (AD35). The present result was comparable with our previous nding, where prenatal BPA exposure at 5 mg/kg/day induced anxietyrelated behavior and impaired learning and memory function 41 . The open eld test is considered to cause anxiety in animals due to social isolation and fear of the novel environment, and the outcome can be altered based on the lighting condition 42,43 .…”
Section: Discussionsupporting
confidence: 93%
“…We speculate that the outcome is also related to regulating GluN2A and GluN2B in the hippocampus. In addition, our previous report has shown that the GluN2A and GluN2B protein levels in the postsynaptic membrane were decreased in the BPA-exposed AD35 rat's hippocampus 41 . Further, this study will observe the prenatal BPA effect on the activity of the GluN2A and GluN2B at a cytoplasmic level in AD35 rat hippocampus only.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations